ANALYSIS OF SOLUTIONS TO REDUCE THE IMPACT OF VEHICLE TRANSPORT ON THE ENVIRONMENT (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
To reduce the negative impact of industry and transport as much as possible, to achieve implementation of large-scale activities in enterprises and organizations and, as a result, to improve the level of atmospheric air quality. 10% reduction of pollutant emissions into the atmosphere (including 7% from transport and 3% from industry); 80 percent of vehicles use gas fuel and to ensure transfer to work one other alternative energy